1999
DOI: 10.1126/science.285.5433.1573
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Nonmevalonate Pathway of Isoprenoid Biosynthesis as Antimalarial Drugs

Abstract: A mevalonate-independent pathway of isoprenoid biosynthesis present in Plasmodium falciparum was shown to represent an effective target for chemotherapy of malaria. This pathway includes 1-deoxy-D-xylulose 5-phosphate (DOXP) as a key metabolite. The presence of two genes encoding the enzymes DOXP synthase and DOXP reductoisomerase suggests that isoprenoid biosynthesis in P. falciparum depends on the DOXP pathway. This pathway is probably located in the apicoplast. The recombinant P. falciparum DOXP reductoisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
947
0
24

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,089 publications
(998 citation statements)
references
References 28 publications
17
947
0
24
Order By: Relevance
“…Indeed, fosmidomycin and its derivative FR-900098 inhibit DXP reductoisomerase, and has been recently shown to possess antiPlasmodium activity in vitro (Jomaa et al 1999). Along the same lines, the yeast-type phosphomevalonate kinase in Borrelia, which thus far appears to have only distant paralogs in humans, or the replacement for IPPI, when it is identified, might be promising targets for anti-Lyme Disease therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fosmidomycin and its derivative FR-900098 inhibit DXP reductoisomerase, and has been recently shown to possess antiPlasmodium activity in vitro (Jomaa et al 1999). Along the same lines, the yeast-type phosphomevalonate kinase in Borrelia, which thus far appears to have only distant paralogs in humans, or the replacement for IPPI, when it is identified, might be promising targets for anti-Lyme Disease therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Lysobisphosphatidic acid and phosphoinositides regulate release of VSV nucleocapsid into cytoplasm [13] SigD/SopB is a type III bacterial derived phosphoinositide phosphatase [29,112] Molecular species of phosphatidylcholine and phosphatidylethanolamine are altered in host plasmamembrane after Plasmodium infection [116] GP Ethanolamine phospholipids required for Sindbis virus production [111] Intracellular mycobacteria release a heterogeneous mixture of lipids [27,113] Growth arrest of Plasmodium [117] and Toxoplasma [85] by disruption of phosphatidylcholine synthesis Semliki Forest virus mRNA capping enzyme requires association with anionic membrane phospholipids for activity [14] Phosphatidylinositol mannosides stimulate fusion of early endosomes with mycobacterial phagosomes [30] Glycosylated phosphatidylinositol causes phagosome maturation arrest [114] SapM, a mycobacterial derived phosphatase hydrolyses PI3P contributing to inhibition of phagolysosome maturation [115] Sphingosine 1-kinase is recruited to nascent phagosomes [118] Inhibition of sphingolipid biosynthesis in T. gondii blocks replication [119] SP Sphingomyelin metabolism important for P. falciparum development [120] Inhibition of cholesterol biosynthesis inhibits Hepatitis C virus RNA replication [15] Inhibition of cholesterol acquisition by the host lowers T. gondii replication [40] ST Cholesterol esterification essential for optimal T. gondii proliferation [121,122] Isopreonoid synthesis inhibitors with anti-malarial [123] and anti-T. gondii activity [124] PR Block of protein farnesylation as antiapicomplexan therapies [125] 5…”
Section: Glmentioning
confidence: 99%
“…Jomaa and co-workers demonstrated that fosmidomycin and its derivate FR900098, are able to inhibit the growth of P. falciparum in culture and to cure mice infected with the related malaria parasite, P. vinckei (Jomaa et al 1999). Recent field trials in humans have also demonstrated the effectiveness of fosmidomycin in the treatment of human malarial infections, but it has to be administered for more than four days when used alone (Missinou et al 2002, Borrmann et al 2005.…”
mentioning
confidence: 99%
“…Discovery of the MEP pathway for isoprenoid biosynthesis in P. falciparum revealed several antimalarial drug targets (Jomaa et al 1999). Jomaa and co-workers demonstrated that fosmidomycin and its derivate FR900098, are able to inhibit the growth of P. falciparum in culture and to cure mice infected with the related malaria parasite, P. vinckei (Jomaa et al 1999).…”
mentioning
confidence: 99%